Creating the Identity of a Lithuanian Social Business Enterprise - Stonkienė, Marija (Information & Media, 2023)
In Lithuania social enterprise as a social category is formed through defined legal social enterprise criteria and their detailed requirements. This suggests that the criteria for the legal definition of a social business enterprise form the identity referents of a social enterprise as a social category.Between 2018 and 2021, seven law projects were submitted to the parliament of Lithuania that aimed to establish criteria defining social business enterprises. Study of these documents aims to identify criteria for a legal definition of Lithuanian social business enterprises that form the defining attributes of the identity of these enterprises, important for the organizational communication of the social business enterprise. The study revealed that the set of legal criteria – entrepreneurship (doing business), social goals aimed at solving social problems and activity stakeholder involvement – define social business enterprises. This exhibits that Lithuanian social business enterprises are institutionalized as hybrid organizations. The assessment of these identity referents showed that their use in the communication of the organization does not ensure the separation of the social enterprise from the subjects of the non-market subsector of the social economy. It has been observed that the exclusion of a social enterprise from other entities can be constructed by elements detailing the referents, often depending on the success of the company’s activities. This ultimately indicates shortcomings in the legal definition of social economic enterprises in Lithuania.
Keywords: social business enterprise; organizational identity; hybrid identity; identity references; Lithuania